Conditions of endotracheal intubation with and without muscle relaxant in children - Nermina Rizvanović; Senada Čaušević; Adisa Šabanović (Medicinski glasnik, 2017)
Aim: To compare intubation conditions and hemodynamic response of two induction regimens, with or without muscle relaxant using a combination of either fentanyl and propofol or propofol and suxamethonium. Methods: A total of 80 children aged 4-12 years were enrolled in a prospective randomized double-blinded study. Children were randomly allocated in two equal groups. In group F induction was done with fentanyl and propofol, while propofol and suxamethonium were used in group S. Intubation conditions were assessed using Copenhagen Consensus Score (CCS), based on ease of laryngoscopy, position of vocal cords, degree of coughing, jaw relaxation and limb movements. Systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP) and heart rate (HR) were observed at preinduction, postinduction and postintubation at 1, 3 and 5 minute. Results: Clinically acceptable CCS was found in 95% of patients in group F versus 100% in group S. Intubation conditions were excellent in 85%, good in 10% and poor in 5% of patients in group F. In the group F, signifficantly lower SBP and MAP postinduction and postintubation at 1 and 3 minute, and lower DBP postinduction and postintubation at 1 minute (p<0.05) was found comparing to group S. In group S, significantly higher postinduction and postintubation HR at 1 minute was found comparing to group F (p<0.05). Conclusion: Induction combination fentanyl-propofol provide acceptable intubation conditions comparable with suxamethonium in children. This induction regimen ensures better hemodynamic stability associated with endotracheal intubation. It could be recommended for intubation when muscle relaxants are not indicated.
Keywords: pediatric anesthesia; fentanyl; propofol; neuromuscular block; suxamethonium